2017
DOI: 10.1177/1940082917702383
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Distribution, and Conservation Status of Peperomia (Piperaceae) in the State of Veracruz, Mexico

Abstract: We present an overview of the diversity, distribution, and conservation status of all 60 species of the genus Peperomia (''radiator plants,'' Piperaceae), which are currently known from the state of Veracruz in Mexico, including a taxonomically updated reference list that includes information about life form, overall distribution, endemism, and occurrence in Mexican states and municipalities of Veracruz. Specifically, for this latter state, we provide information on elevational range, habitat, and distinguishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 39 publications
1
17
0
11
Order By: Relevance
“…Ethnobotanical, taxonomic, and ecological relevance of this family for Oaxaca is remarkable due to the fact that many species are gathered from the wild. The ecological statuses of most of them are unknown; nevertheless, they grow in specific microhabitats, or on specific phorophytes, and our qualitative evaluation indicates that their populations are scarce (Table 1), so it is possible they are at risk due to deforestation, habitat fragmentation, or over-gathering, as indicated in other studies (Arellanes et al, 2013;Blancas, Casas, Pe´rez-Salicrup, Caballero, & Vega, 2013;Vergara-Rodr ıguez et al, 2017). Commercialization could be another important cause of increasing over-gathering practices.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Ethnobotanical, taxonomic, and ecological relevance of this family for Oaxaca is remarkable due to the fact that many species are gathered from the wild. The ecological statuses of most of them are unknown; nevertheless, they grow in specific microhabitats, or on specific phorophytes, and our qualitative evaluation indicates that their populations are scarce (Table 1), so it is possible they are at risk due to deforestation, habitat fragmentation, or over-gathering, as indicated in other studies (Arellanes et al, 2013;Blancas, Casas, Pe´rez-Salicrup, Caballero, & Vega, 2013;Vergara-Rodr ıguez et al, 2017). Commercialization could be another important cause of increasing over-gathering practices.…”
Section: Discussionmentioning
confidence: 68%
“…Even when some of the species are relevant in many ethnic and Mestizo groups because of their medicinal, food, or condiment uses, previous studies only reported one or few species (Arellanes et al, 2013;Blancas et al, 2013;Browner, 1985;Caballero, Corte´s, Mart ınez-Alfaro, & Lira-Saade, 2004;Frei et al, 1998;Geck, 2018;Geck et al, 2016;Giovannini & Heinrich, 2009; Luna-Jose´& Rend on- Salinas-Espinoza et al, 2017;Solis-Rojas, 2006), and they correspond to 19 of the 106 species (Villaseñor, 2016) reported for this state (Caballero et al, 2004;Frei et al, 1998;Geck, 2018;Geck et al, 2016;Giovannini & Heinrich, 2009; Luna-Jose´& Rend on- Aguilar, 2012;PerezNicolas et al, 2017PerezNicolas et al, , 2018RangelLanda et al, 2016RangelLanda et al, , 2017Vergara-Rodr ıguez et al, 2017). Among these, the most mentioned is P. auritum and in minor proportion P. peltilimba; the rest of the species are named only once (Table 2).…”
Section: Discussionmentioning
confidence: 95%
“…Más de 50 % de los municipios no contaba con registros de angiospermas epífitas, y aunque la vegetación que se encuentra en algunos de ellos no es la más favorable para el desarrollo de plantas con este hábito, se ha observado que especies como Tillandsia recurvata (L.) L. y T. circinnatioides Matuda están presentes en zonas áridas o con alto grado de perturbación, por lo que la ausencia de registros para estas áreas parece estar más relacionada con la falta de exploración botánica. En lo que se refiere a los siete nuevos registros para la entidad, tres pertenecen a Peperomia (Piperaceae), género con morfología compleja y cuyas especies son difíciles de identificar, sobre todo por la falta de claves generales para hacerlo, pues la mayoría de éstas están enfocadas a taxa de regiones muy específicas (Vergara-Rodríguez 2009, Schouppe 2010, Vergara-Rodríguez et al 2017, Jimeno-Sevilla et al 2018. Anthurium schlechtendalii Kunth subsp.…”
Section: Discussionunclassified
“…En México, la mayor parte de los estudios sobre estas plantas se ha enfocado en aspectos ecológicos o de conservación (Hietz & Hietz-Seifert 1995a, b, Wolf & Konings 2001, Flores-Palacios & García-Franco 2004, 2006, Wolf 2005, Martínez-Meléndez et al 2008, Krömer et al 2013a) y aquellos que aportan información al conocimiento florístico se han dirigido a algunas familias o géneros particulares (Hágsater & Salazar 1990, Espejo-Serna & López-Ferrari 1997, Halbinger & Soto 1997, Hágsater & Soto 2002, Hágsater & Sánchez 2008, Vergara-Rodríguez 2009, Schouppe 2010, Krömer et al 2013b, Palmas-Pérez et al 2013, Vergara-Rodríguez et al 2017, a regiones específicas (Limón 2008, Morales 2008, Martínez-Meléndez et al 2009, Pérez-Bravo et al 2010, Salazar-Rodríguez 2010, Ceja-Romero et al 2012, Gomez-Escamilla et al 2019) o a estados como Chiapas, Guerrero, Hidalgo, Morelos y Veracruz (Hietz & Hietz-Seifert 1994, Espejo et al 2002, Pulido-Esparza et al 2004, Espejo-Serna et al 2005a, Wolf & Flamenco-Sandoval 2005, Ceja-Romero et al 2010, Flores-Palacios et al 2011.…”
unclassified
“…The species of Peperomia are characterized by bisexual flowers (sessile, sunk in rachis) in spike inflorescence and lateral or terminal stigma which is usually penicillate. The genus is often considered as one of the most species rich genera of angiosperms [7][8][9][10]. Peperomia pellucida (L.) Kunth ( fig.…”
Section: Introductionmentioning
confidence: 99%